Intention to leave the nursing profession and its relation with work climate and demographic characteristics - Fatemeh Sharififard; Hamid Asayesh; Hossein Rahmani-Anark; Mostafa Qorbani; Valiollah Akbari; Hossein Jafarizadeh (Wolters Kluwer Medknow Publications, 2019)
Background: Because of the importance of staff shortage in health systems, considering the intention to leave the job and its related factors among nurses is very important. The aim of this study was to identify the association between the intention to leave the nursing profession and work climate and demographic characteristics. Materials and Methods: A cross-sectional survey was conducted among 206 nurses, by random sampling method from six hospitals (response rate = 92%). A set of self-administered questionnaires were applied for the evaluation of intention to leave and work climate. Results: The high level of intention to leave the profession was expressed by 23.70% of the participants; 25.10% of the participants had the moderate intention. Data analysis revealed that work climate, type of employment, marital status, and overtime working were significant predictors of nurses' intention to leave after controlling other independent variables (R2 = 0.10, p < 0.001). Conclusions: It was found that work climate and some demographic characteristics can be seen as indicators for intention to leave among nurses; therefore, considering the so-called variables is required. Further studies are needed to identify other aspects of the issue.